return rates - Morganti, Michelangelo; Rubolini, D.; Lardelli, Roberto; Liechti, Felix; Boano, Giovanni; Tomassetto, Erika; Ferri, Mauro; Caffi, Mario; Saino, Nicola; Ambrosini, Roberto (Dryad Digital Repository, 2017)
table showing return rates of geolocator and control birds in form of aggregated data (one record per year, study site and species of birds) for Italian and Swiss study sites.This data were used for the analysis shown in Table 4 of main text.